PENATALAKSANAAN OSTEOARTHRITIS DAN HIPERTENSI PADA WANITA USIA 62 TAHUN DENGAN PRINSIP PENDEKATAN KEDOKTERAN KELUARGA DI PUSKESMAS KEDATON - Ananti, Anggini T; Effendi, R.E. Rizal (CV. Jasa Sukses Abadi, 2024)
Osteoarthritis is a chronic disease characterized by damage to joint and cartilage. This causes the bones to rub against each other, causing stiffness, pain and impaired movement. Degenerative diseases are non-communicable diseases (PTM) that are chronic and related to genetic, environmental and behavioral factors. The study uses a method in the form of case reports with primary data were obtained from anamnesis, physical examination, and home visits. Secondary data obtained from medical records. The assessment is based on holistic diagnostics from the initial, process, and final studies quantitatively and qualitatively. Patient Mrs. M, sixty-two years old, with complaints of pain in the left knee since two years ago. The complaint began with pain in his knee, especially when walking and getting up from a sitting position to standing, so that in the last two weeks it greatly hampered his activities. In the patient's personal history, she often lifts heavy burdens because she has to care for her husband who has been sick due to an accident 4 years ago. The patient also has a history of hypertension since 3 years ago. The evaluation results showed reduced clinical symptoms and increased knowledge about the disease. Obtained internal and external risk factors in patients. Increased knowledge about disease in patients and prevention of hypertension and osteoarthritis as evidenced by an increase in pretest-posttest scores by 30 points from 60 to 90 points.